AMID THE THREAT OF CYBERCRIME - Tandana, Ester Agustini (QUAERENS: Journal of Theology and Christianity Studies, 2022)
Online romance scams have emerged as a pervasive and emotionally devastating form of fraud in the digital age. These scams exploit individuals emotionally, financially, and psychologically, leaving victims traumatized and financially crippled. Online romance scams involve perpetrators assuming false identities to establish fake romantic relationships with unsuspecting individuals, ultimately leading to financial exploitation. This research delves into the concept of pastoral care as a holistic approach to mitigating the risk of online romance scams and supporting victims. Online romance scams represent a modern challenge with profound emotional and financial consequences. Internet love scams are a sort of organized crime that takes place on the internet. It may be viewed as a crime involving a deliberate breach of the law using deceit in order to obtain monetary advantage from specific victims. Many examples of Internet love scams go undetected. Pastoral care, with its holistic approach, offers a promising avenue for prevention and support. By addressing emotional, psychological, spiritual, and financial aspects, pastoral care can empower individuals and communities to guard against these scams and provide much-needed solace and recovery for victims. Additionally, the impact of pastoral care contributes to the resilience of communities in the face of this evolving threat.